PAI TEACHER'S STRATEGY FOR STUDENTS' CHARACTER GROWTH - Nisa, Melynda Khoirun; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic religious education teachers play an important role in shaping the character of school students. Because an Islamic teacher is a teacher who can educate the personality of his students according to Islamic law. The role of Islamic religious teachers is to shape the behavior of students who were previously less capable to become better and those who were previously good to become even better. Therefore, Islamic religious teachers, apart from providing religious knowledge, also help shape students' character according to Islamic law and Indonesian culture. This research aims to determine the contribution of Islamic religious education teachers in forming student character. This research is qualitative research, namely library research which uses books and other literature as the main topic. The research results show that Islamic teachers are one of the pioneers in the success and formation of students' personalities, because they play an important role as sponsors or imitators in implementing personality formation in schools. The contribution of Islamic religious education teachers in shaping student character, namely empowerment, role modeling, intervention, integration, sekrening.